MEDIA AND COMMUNICATION (R)EVOLUTION - Trivic, Natalija (Politeia, 2020)
The accelerated development of the information society from the end of the 20th and the beginning of the 21st century had a direct impact on the media and media communication. Traditional media (press, radio, television) and one-way communication with the audience are increasingly being replaced by new, digital media, by a platform that enables the  interactivity of audience in communication.The Internet as a new medium and a platform for new media communication has offered a new way of communicating with an audience that is no longer a passive recipient of information but an active participant in the process. The interactivity of audience through new media forms of expression (portals, social networks, blogs, vlogs) is a basic feature of modern communication.  This paper aims at analysing, through defining the Internet as a new medium, new media forms of communication that have involved the audience in the interactive exchange of information and opinions, and thus completely and irreversibly changed the organisation and functioning of the media.The paper primarily examines new forms of media communication conditioned by a new media, digital-platform-based environment. The analysis shows that new media communication has opened the space for an audience to become an active participant in public communication, thus directly affecting certain spheres of social life. At any moment, every individual can be a media content producer and interactive participant in new media communication.
Keywords: Media; Internet; Revolution; Communication